2018
DOI: 10.20524/aog.2018.0315
|View full text |Cite
|
Sign up to set email alerts
|

Medical hypothesis: speculating on the pathogenesis of acute diverticulitis

Abstract: The pathogenetic process of acute diverticulitis remains speculative. According to the most widely accepted theory, the mechanism involved is “traumatic” damage to the mucosa due to fecolith impaction, as occurs in large diverticula. However, not uncommonly, diverticulitis develops in young patients with only few and small diverticula, where fecolith trapping is very unlikely. Therefore, another theory is necessary to clarify this process. A possible explanation could be “ischemic” damage. According to this th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
1
14
0
2
Order By: Relevance
“…However, they remain largely neglected in the therapeutic approaches to symptomatic DD patients in clinical practice [135]. Experimental data have clearly demonstrated that hyper-contractions of circular muscle in the sigmoid tract with DD are reduced by anticholinergic drugs, although a high dose may be necessary [100]. Unfortunately, only data from old, and often not well-designed, studies are available, and the scant interest of pharmaceutical industries in research in this field appears to be unjustified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they remain largely neglected in the therapeutic approaches to symptomatic DD patients in clinical practice [135]. Experimental data have clearly demonstrated that hyper-contractions of circular muscle in the sigmoid tract with DD are reduced by anticholinergic drugs, although a high dose may be necessary [100]. Unfortunately, only data from old, and often not well-designed, studies are available, and the scant interest of pharmaceutical industries in research in this field appears to be unjustified.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial infection then develops until micro-perforation occurs [97-99]. Recently, the role of ischemic damage, without involvement of fecoliths or infection, has been pointed out [100]. According to this novel hypothesis, there is a temporary (or recurrent) compression of vasa recta in the “neck” of the diverticulum due to a prolonged and/or marked contractile spike of colon with ischemia, particularly in diminutive diverticula, than micro-perforation at the apex of the sac occurs, with or without secondary infection from fecal bacteria [100].…”
Section: Diverticulitismentioning
confidence: 99%
“…For example, we know that the majority of patients having acute complicated diverticulitis (ACD) are at the first appearance of the disease, without any significant symptom before complication [15]. Recently, a review article underlines two other mechanisms explaining the AD occurrence, the "traumatic" and the "ischemic" hypotheses [16]. The "traumatic" mechanism takes into account the damage to the mucosa due to fecalith impaction, which occurs in the large diverticula.…”
Section: Inflammation and Pathogenesis Of Acute Diverticulitismentioning
confidence: 99%
“…Another postulated mechanism for the development of acute diverticulitis is a microperforation at the fundus of the diverticulum leading to inflammation [8]. Very recently, an ischemic pathogenesis has been hypothesized [9]. The trigger of the ischemic process may be a long-lasting (or recurrent) compression of vasa recta in the "neck" of the diverticulum due to a prolonged and marked contractile activity of the colon.…”
Section: Clinical Pictures Of Diverticular Diseasementioning
confidence: 99%
“…Indeed, the tiny "neck" of the diverticulum passes through the circular muscle of the bowel wall and could be abnormally compressed, leading to mucosal ischemia at the apex of the sac or even microperforation. The "traumatic" and "ischemic" mechanisms of acute diverticulitis may not be mutually exclusive since they may act in different patients (old versus young) or in different types (large versus diminutive) diverticula [9].…”
Section: Clinical Pictures Of Diverticular Diseasementioning
confidence: 99%